ĐÁNH GIÁ NGUY CƠ BỊ TỔN THƯƠNG DO SÓNG THẦN CHO KHU VỰC ĐÔ THỊ THÀNH PHỐ NHA TRANG - Phương, Nguyễn Hồng; Truyền, Phạm Thế; MOIRET, ADRIEN (Vietnam Journal of Earth Sciences, 2011)
Assessment of tsunami vulnerability for an urban area of Nha Trang cityIn this paper a new methodology for tsunami vulnerability assessment for Vietnam is proposed. Based on Multi-Criteriaanalysis technique, the methodology allows semi-quantitatively assess the vulnerability of a coastal urban area being affected by future tsunamis. The advantage of the methodology is simplicity, flexible to the changes of conditions of reality and allowing application of a Geographic Information System (GIS). The procedure can be applied to any coastal zone under tsunami threat. The methodology is pilot tested in a coastal urban area of Nha Trang city. The results are presented within a GIS in terms of vulnerability maps for such aspects as building environment and population. The results show prospects in the new direction of tsunami risk study in Vietnam and provide important implications for coastal risk assessment, resource allocation as well as disaster management planning.